2023
DOI: 10.1111/dmcn.15673
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of spoken language comprehension and functional communication in children with cerebral palsy: A prospective cohort study

Abstract: AimTo investigate spoken language comprehension (SLC), single‐word comprehension (SWC), functional communication development, and their determinants, in children with cerebral palsy.MethodThis was a prospective cohort study in the Netherlands spanning 2 years 6 months. The main outcomes were SLC and SWC, assessed by the Computer‐Based instrument for Low motor Language Testing (C‐BiLLT) and the Peabody Picture Vocabulary Test‐III‐NL (PPVT‐III‐NL) respectively; and functional communication, measured by a subscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Both caregivers and clinicians viewed the C-BiLLT-CAN with considerable optimism, with caregivers anticipating a variety of positive effects of results across a breadth of environments and clinicians anticipating consequent improvements in service provision. These results capture the latent clinical usefulness of the C-BiLLT-CAN and also foreshadow a role in research endeavours aimed at understanding the promotion of positive outcomes for children withCP and LFS (48,49). A recent scoping review by Chagas and colleagues(50) found that few longitudinal studies on the development of children with CP systematically tracked changes in levels of or factors in uencing communication, Visual and auditory access modi cations may also improve feasibility of the C-BiLLT-CAN for the considerable proportion of children with CP and LFS who informed survey responses that also had a visual impairment such as CVI (e.g., 55) until a specially designed version of the test, currently under consideration, is available to meet the particular needs of these children.Caregivers and clinicians assigned moderate to high ratings of importance to several additional response methods not currently supported by the C-BiLLT-CAN.…”
supporting
confidence: 53%
“…Both caregivers and clinicians viewed the C-BiLLT-CAN with considerable optimism, with caregivers anticipating a variety of positive effects of results across a breadth of environments and clinicians anticipating consequent improvements in service provision. These results capture the latent clinical usefulness of the C-BiLLT-CAN and also foreshadow a role in research endeavours aimed at understanding the promotion of positive outcomes for children withCP and LFS (48,49). A recent scoping review by Chagas and colleagues(50) found that few longitudinal studies on the development of children with CP systematically tracked changes in levels of or factors in uencing communication, Visual and auditory access modi cations may also improve feasibility of the C-BiLLT-CAN for the considerable proportion of children with CP and LFS who informed survey responses that also had a visual impairment such as CVI (e.g., 55) until a specially designed version of the test, currently under consideration, is available to meet the particular needs of these children.Caregivers and clinicians assigned moderate to high ratings of importance to several additional response methods not currently supported by the C-BiLLT-CAN.…”
supporting
confidence: 53%